1982
DOI: 10.1302/0301-620x.64b1.7068728
|View full text |Cite
|
Sign up to set email alerts
|

The long-term results of unrepaired tears of the posterior cruciate ligament

Abstract: A group of 20 patients with ruptures of the posterior cruciate ligament treated either by early mobilisation or by plaster immobilisation is described. The functional results bore no relationship to the degree of laxity of the ligament and 18 of the 20 patients considered that their symptoms did not warrant the discomfort and inconvenience ofreconstruction ofthe ligament. It is suggested that many patients with posterior cruciate insufficiency have a good functional result, and that the place of routine repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
119
0
4

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(127 citation statements)
references
References 0 publications
4
119
0
4
Order By: Relevance
“…Many authors have reported on the results of nonoperative management of the PCL-deficient knee [6,13,20,23,25,[28][29][30][31][32][33][34][35][36][37]. Boynton and Tietjens [33] retrospectively evaluated 38 patients with isolated, nonoperatively treated PCL injuries at a mean follow-up of 13.4 years (range 5 to 38 years).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many authors have reported on the results of nonoperative management of the PCL-deficient knee [6,13,20,23,25,[28][29][30][31][32][33][34][35][36][37]. Boynton and Tietjens [33] retrospectively evaluated 38 patients with isolated, nonoperatively treated PCL injuries at a mean follow-up of 13.4 years (range 5 to 38 years).…”
Section: Discussionmentioning
confidence: 99%
“…Most reports on PCL injuries are retrospective studies of acute and chronic PCL injuries that include a mixed population of both isolated and combined ligamentous injuries of the knee [5,11,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Based on these reports, it is difficult to derive a conclusion regarding the ideal management of patients with acute, isolated PCL injuries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acute suture is recommended by several authors (Fetto & Marshall 1980, Hejgaard et al 1982, Lysholm et al 1982, O'Donoghue 1959, Palmer 1938, but the results do not differ much from those of conservative treatment (Balkfors 1982, Dandy & Pusey 1982, McDaniel & Dameron 1980. Because of the rapid onset of atrophy in injuries to the mid-substance of the ACL, resection of the cruciate ligament has been recommended (Kennedy et al 1974), while surgeons in sports medicine recommend acute reconstruction using a modified Jones procedure (Eriksson 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is due particularly to deficient elucidation of the spontaneous course of untreated or insufficiently treated ligament injuries. According t o some authors, however, the course is not as unfavourable as previously assumed (Balkfors 1982, Dandy & Pusey 1982, McDaniel & Dameron 1980. With the aid of an accurate, prospective stress radiographic measuring technique we have been able to describe the long-term course of old ligament injuries to the knee joint, with a particular view to changes in passive instabilities.…”
mentioning
confidence: 93%